De middeleeuwse bedelordearchitectuur in Nederland (Bulletin KNOB, 2002)
This preliminary synthesis concerning the architecture of the Mendicants - Franciscans, Dominicans, Carmelites and Augustinian Friars - in the Netherlands is the result of a two-year research fellowship at Leiden University (1999-2001).From the 13th to the early 16th century 57 friaries were founded in 43 different Dutch towns: 29 by the Franciscans, 14 by the Dominicans, 8 by the Carmelites and 6 by the Augustinian Friars. Minimal information was found for the buildings of 27 friaries; only 13 churches have survived. Little is known of the first churches. Excavations at three sites show early evidence for a diversity in building types, from the single nave to the aisled basilica.The first church of the Franciscans at Maastricht had a plan that was directly based on the church of Assisi. For a series of churches dating from the second half of the 13th century and completed during the 14th century, the most common type is the aisled basilica with a polygonal choir, covered with stone ribbed vaults that were strengthened with flying buttresses, and without tower or transept.The second church of the Franciscans at Maastricht as well as the churches of the Dominicans at Maastricht and Zutphen are the three best preserved churches of this series. The little brick church of the Franciscan at Bolsward was covered by a timber barrel vault.A second wave of building in the 15th century, was the result of new foundations as well as the reform of old friaries, which was imposed by late medieval urban society and supported by the politics of the dukes of Burgundy. The hall-church (a building with two or three naves of equal height) covered by wooden barrel vaults became the most common type at this time.The churches of the Dominicans at The Hague, Leeuwarden and Zwolle, of the Augustinian friars at Dordrecht and of the Franciscans at Deventer, Kampen, Roermond and Weert are the best-preserved churches of this series. Only the early 16th-century church of the Carmelites at Utrecht was an aisled basilica and had a transept.The most fascinating characteristic of late medieval mendicant architecture is the succession of extensions, sometimes ingeniously contrived by adding naves and chapels for families, guilds and confraternities. As a result of this building investigation - with new information provided both by dendrochronological study and archaeological excavations -, it was possible to reconstruct the thriving growth process of some late medieval churches.Despite other variations in plan, mendicant churches always consisted of two different parts separated by a screen. To the east is the choir, reserved for the liturgical offices of the friars. Most commonly the choir has a polygonal apse and high windows providing generous light. To the west is the preaching area, including one or several naves, sometime with side chapels. This public part of the church was not only used for offices and for preaching, but also served as a burial place as well as a room for civil meetings. The Franciscan church at Maastricht is the only one where part of the screen is still conserved.Only a few medieval buildings of mendicants' convents are conserved in the Netherlands. A complete cloister with a garth and four galleries can only be seen at Zwolle and Haarlem. Other remains of conventual buildings survive at Zutphen, Maastricht, The Hague, Leeuwarden, Amersfoort and Dordrecht. They provide not enough information to reconstruct the organisation of daily life and its evolution from the 13th to the 16th century.In comparison with parish and collegiate churches, those of the mendicants were easy to recognize in the urban landscape, thanks to the simplicity of their building concepts (no towers, transepts, ambulatory or radiating chapels), the economy of materials (stone, brick and wood) and the near-absence of sculpted decoration (excepting occasional bosses and corbels). This relative ‘poverty’ not only characterised mendicant architecture, but also presented a strong contrast to the furnishings.Insofar as it is possible to imagine the church interiors, we know that they were filled with tombs, altars supporting rich retables, expensive stained glass windows, mural and vault paintings, and other types of decoration - in other words, all the possible gifts made by the burghers and members of the confraternities who wished to rest ‘at the Friars’ for all eternity.As indispensable complement of this article, a catalogue describing the medieval friaries of mendicants in the Low Countries - with detailed chronology and complete literature - can be found in: Th. Coomans, ‘L'architecture médiévale des ordres mendicants (Franciscains, Dominicains, Carmes et Augustins) en Belgique et aux Pays-Bas’, Revue Belge d'Archéologie et d'Histoire de l'Art, 70, 2001, p. 3-108.